2019
DOI: 10.37715/rme.v2i1.952
|View full text |Cite
|
Sign up to set email alerts
|

Stock Price Behavior Around Cum-Dividend Date of Indonesia Blue Chips Stocks

Abstract: This study tests whether there are significant stock prices changes around the cum-dividend date. In particular, it examines the stock price movement of two days before and two days after the cum-dividend date. It uses an event study methodology. The population of this study are all companies in the LQ45 listed at Indonesia stock exchange for the year 2017 and the sample consists of 38 companies. Abnormal return is measured using the single index model. Results show that there are no significant abnormal retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Previous research has shown that prices around the cumulative date do not provide abnormal returns, which means that there is no significant increase in stock prices [12]. Nevertheless, the research was only one and two days before and after the cumulative date.…”
Section: Differences In Share Prices Regarding Cash Dividend Announce...mentioning
confidence: 86%
See 2 more Smart Citations
“…Previous research has shown that prices around the cumulative date do not provide abnormal returns, which means that there is no significant increase in stock prices [12]. Nevertheless, the research was only one and two days before and after the cumulative date.…”
Section: Differences In Share Prices Regarding Cash Dividend Announce...mentioning
confidence: 86%
“…There are differences in the policy of determining the number of cash dividends distributed in western countries and Indonesia [12]. In western countries, e.g., the US market, London market, German market, and Greek market, the dividend is determined by the management while in Indonesia it is determined at the shareholders' meeting.…”
Section: Cash Dividendmentioning
confidence: 99%
See 1 more Smart Citation
“…Melalui hasil pengujian signifikansi Average Abnormal Return tersebut, diketahui bahwa uji t secara konsisten didukung oleh sebagian besar uji statistik lainnya. Hasil temuan ini sejalan dengan hasil penelitian yang sudah dilakukan sebelumnya oleh Lavista & Utami (2017) serta Lestari, Arif, dan Wijayantini (2018), bahwa terdapat indikasi adanya abnormal return positif pada satu sampai dua hari menjelang tanggal cum-dividend. Hal ini dapat disebabkan karena tanggal cum-dividend merupakan tanggal terakhir di mana investor yang akan membeli saham suatu perusahaan dapat memiliki hak dalam pembagian dividen perusahaan tersebut, sehingga aksi pembelian saham suatu perusahaan yang akan membagikan dividen tersebut meningkat.…”
Section: Hasil Dan Pembahasanunclassified